A Fine-Grained Mobile Data Security Model - Yubin Yang; Liming Cheng (Dianxin kexue, 2014)
A kind of fine-grained security model for mobile data was proposed, tagged the mobile data and mobile applications in the intelligent terminal and the mobile access gateway/server, to control the operation of mobile data, and achieve the purpose of mobile data security isolation. Thus fine-grained security for mobile data management capabilities were achieved. The model was consisted of mobile data management module and the label control management module. The mobile data management module identified the user permissions and level of data privacy through the label to control the operation of mobile application of mobile data. The creating, modifying, storing and transmitting of the data label and application label were controlled and managed by the label control management module. Experiments on the Android device were carried out, and the security of the model was confirmed.